Conception et réalisation d'une application pour la gestion des Rendez-Vous - ABID, Hedda; MERABET, Chahrazed; BEDDA, Ilias (university of eloued جامعة الوادي, 2016)
وظشا لأهم تُ انىقج ف ح اُحىا انشخص تُ و انعمه تُ، س كُىن انهذف مه عمهىا هزا حطى شَ حطب قُ حَخى عه مزكشة لإداسة انىقج و انخزك شُ بانمىاع ذُ و نهمساعذة عه إوجاص انمهاو انمشاد انق اُو بها ف الأوقاث انمحذدة. وخمى أن وخمكه مه إضافت نمست قذ لا حخىاجذ ف أغهب انخطب قُاث انمشابهت ألا و ه انخزك شُ بمىاع ذُ انصلاة. وش ذَ أن حَخى هزا انخطب قُ عه وظشة ىَم تُ، أسبىع تُ و أخشي شهش تَ نهمىاع ذُ و إرا أمكه وظشة مهى تُ وخخضل ف هُا انىظشة بإظهاس ساعاث انعمم فقطGiven the importance of time in our personal and professional lives, the main objective of this work is to develop an application featuring a Time Management Schedule, Appointment reminder helping us to accomplish scheduled tasks at the best time. We hope that we would be able to provide an added value to existing applications which don’t include, for instance, a Prayer times reminder. We hope this application can help fostering daily, weekly and monthly views of our schedule time with a professional view limited to the work hours.
licence mémoire informatique